2012
DOI: 10.1523/jneurosci.3896-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Interception of a Moving Visual Target after a Spatiotemporal Perturbation

Abstract: Animals can make saccadic eye movements to intercept a moving object at the right place and time. Such interceptive saccades indicate that, despite variable sensorimotor delays, the brain is able to estimate the current spatiotemporal (hic et nunc) coordinates of a target at saccade end. The present work further tests the robustness of this estimate in the monkey when a change in eye position and a delay are experimentally added before the onset of the saccade and in the absence of visual feedback. These pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…In some trials, eye position was perturbed at occlusion onset through microstimulation in deep SC. Fleuriet and Goffart (2012) showed that, even when the saccades started from a different position than saccades without microstimulation, they always landed near the (occluded) target. Moreover, the subsequent interceptive saccade often adequately compensated for the different amounts of invisible target motion occurring during additional delays induced by the microstimulation.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…In some trials, eye position was perturbed at occlusion onset through microstimulation in deep SC. Fleuriet and Goffart (2012) showed that, even when the saccades started from a different position than saccades without microstimulation, they always landed near the (occluded) target. Moreover, the subsequent interceptive saccade often adequately compensated for the different amounts of invisible target motion occurring during additional delays induced by the microstimulation.…”
mentioning
confidence: 98%
“…A recent study published in The Journal of Neuroscience (Fleuriet and Goffart, 2012) addressed the distinction between these schemes on the basis of experiments involving microstimulation of the SC. Monkeys made interceptive saccades to, and subsequently pursued, moving targets; these targets were occluded during the interceptive saccades.…”
mentioning
confidence: 99%
See 3 more Smart Citations